Development and initial evaluation of the SCI-FI/AT. (May 2015) - Jette, Alan M.; Slavin, Mary D.; Ni, Pengsheng; Kisala, Pamela A.; Tulsky, David S.; Heinemann, Allen W.; Charlifue, Susie; Tate, Denise G.; Fyffe, Denise; Morse, Leslie; Marino, Ralph; Smith, Ian; et al.
Abstract : Objectives: To describe the domain structure and calibration of the Spinal Cord Injury Functional Index for samples using Assistive Technology (SCI-FI/AT) and report the initial psychometric properties of each domain. Design: Cross sectional survey followed by computerized adaptive test (CAT) simulations. Setting: Inpatient and community settings. Participants: A sample of 460 adults with traumatic spinal cord injury (SCI) stratified by level of injury, completeness of injury, and time since injury. Interventions: None Main outcome measure: SCI-FI/AT Results: Confirmatory factor analysis (CFA) and Item response theory (IRT) analyses identified 4 unidimensional SCI-FI/AT domains: Basic Mobility (41 items) Self-care (71 items), Fine Motor Function (35 items), and Ambulation (29 items). High correlations of full item banks with 10-item simulated CATs indicated high accuracy of each CAT in estimating a person's function, and there was high measurement reliability for the simulated CAT scales compared with the full item bank. SCI-FI/AT item difficulties in the domains of Self-care, Fine Motor Function, and Ambulation were less difficult than the same items in the original SCI-FI item banks. Conclusion: With the development of the SCI-FI/AT, clinicians and investigators have available multidimensional assessment scales that evaluate function for users of AT to complement the scales available in the original SCI-FI.